Newborn screening for lysosomal disorders in Brazil: A pilot study using customized fluorimetric assays - Bender,Fernanda (2020)
Abstract Lysosomal storage disorders (LSDs) are a group of genetic disorders characterized by deficiency of specific lysosomal enzymes. In general, patients are clinically normal at birth, and progressively develop severe signs and symptoms. Diagnosis is usually made several years after onset of manifestations, preventing patients to have the benefits of the early treatment. Newborn screening programs are being considered for LSDs to allow early diagnosis and treatment. The present study evaluated the feasibility of a customized screening approach based on modified fluorometric assays with reduced amounts of reagents, substrates and samples for: mucopolysaccharidosis (MPS) type I (MPS I), MPS VI, Fabry, Gaucher, and Pompe diseases. We also evaluated the advantages of including blood chitotriosidase and urinary glycosaminoglycans in the protocol. By the measurement of the specific disease-associated enzymes (plus blood chitotriosidase and urinary glycosaminoglycans) we analyzed 834 de-identified DBS of unselected newborns. No positive case was detected, and the false-positive rates were low. Taking into consideration the limitations of this methodology, we believe that, after defining proper cutoffs, it could be a viable alternative to provide NBS for LSDs by laboratories that may not be able to afford the commercial methods available.